The Role Of Qur'anic Distribution In Islamic Fiscal Policy In Indonesia: A Study Of QS. Al-Hasyr 7, QS. Al Nisa 58 - Muhammad Zainudin; Ahmad Djalaluddin; Rosbianti Rosbianti; Muhammad IbnuAkbarNuryadi; Asep Hikmatullah (Tasyri' : Jurnal Muamalah dan Ekonomi Syariah, 2026)
The persistent inequality in wealth distribution in Indonesia reflects the failure to integrate Islamic normative values into the national fiscal policy framework, even though the Qur'an established comprehensive principles of distribution long before modern fiscal theory emerged. This study aims to analyze and construct the role of Qur’anic distribution principles—specifically Surah al-Hasyr, verse 7, regarding the distribution of wealth, and Surah al-Nisā’, verse 58, regarding amanah—as the normative foundation for Islamic fiscal policy in Indonesia. The study employs a qualitative approach using thematic exegesis (maudhū'i) and library research, through content analysis of classical and contemporary exegetical sources as well as relevant academic literature on Islamic economics. The results indicate that Surah al-Hasyr verse 7 contains a structural imperative prohibiting the concentration of wealth and mandating redistribution through fiscal instruments such as zakat and productive waqf, while Surah an-Nisa’ verse 58 establishes the principle of amanah as the ethical foundation of fiscal governance, demanding competence, transparency, and justice in the management of public finances. The synthesis of these two principles yields a conceptual model of Islamic fiscal policy that integrates distributive objectives with accountable governance mechanisms. This study contributes to enriching the theoretical framework of Islamic economics and provides practical implications for policymakers to formally integrate the instruments of zakat and waqf into the national fiscal system, as well as to strengthen Islamic fiscal institutions based on the principle of amanah.